2005
DOI: 10.1074/jbc.m508189200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Ca2+/Calmodulin-dependent Protein Kinase II Activity by Regulated Interactions with N-Methyl-D-aspartate Receptor NR2B Subunits and α-Actinin

Abstract: Postsynaptic roles of CaMKII␣ in synaptic plasticity are thought to require specific targeting to the postsynaptic density (PSD), a cytoskeletal structure juxtaposed to excitatory synapses that is enriched in neurotransmitter receptors and other signaling proteins. Immunohistochemical studies have revealed a wide range in the amount of CaMKII associated with individual PSDs (4, 5), consistent with a dynamic regulation of PSD targeting. Exogenous, Thr 286 -autophosphorylated CaMKII␣ ([P-T 286 ]CaMKII) binds spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 50 publications
5
61
0
Order By: Relevance
“…In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002). It has also been observed that autophosphorylation of T305/6 inhibits binding of αCaMKII to the PSD and several PSD proteins (Strack et al, 1997b;Leonard et al, 2002;Robison et al, 2005). Furthermore, it has been demonstrated that T305/6 phosphorylation increases the dissociation rate of the kinase from the PSD (Shen et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002). It has also been observed that autophosphorylation of T305/6 inhibits binding of αCaMKII to the PSD and several PSD proteins (Strack et al, 1997b;Leonard et al, 2002;Robison et al, 2005). Furthermore, it has been demonstrated that T305/6 phosphorylation increases the dissociation rate of the kinase from the PSD (Shen et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Like T286 phosphorylation, T305/6 phosphorylation has been shown to modulate protein-protein interactions of CaMKII. Phosphorylation of these residues inhibits kinase binding to isolated PSDs (Strack et al, 1997b), α-actinin (Robison et al, 2005), and the NMDAR subunits NR1 and NR2B (Leonard et al, 2002). In addition, T305/6 phosphorylation increases the dissociation rate of CaMKII from the PSD (Shen et al, 2000), and mimicking phosphorylation on these residues prevents while inhibiting phosphorylation enhances PSD association of the kinase (Elgersma et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Each subunit can bind several postsynaptic proteins (25,26), providing the possibility for the dodecamer holoenzyme to form a multimolecular complex. This binding is often facilitated by autophosphorylation at T286 but does not require subsequent enzymatic activity (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Thr-286 phosphorylation mildly enhances stimulated activity by 10 -20% (26), but also promotes additional Thr-305/ 306 phosphorylation that prevents subsequent Ca 2ϩ /CaM binding (26,31,32,38). By contrast, GluN2B binding actually reduces stimulated activity (10,39), but inhibits Thr-305/306 phosphorylation (10) (for review see Ref. 1).…”
Section: Discussionmentioning
confidence: 99%